Análise de vulnerabilidade ambiental de bacias Periurbanas e a proteção de reservatórios utilizados Em sistemas públicos de abastecimento de água: estudo De caso da bacia do rio Gramame/PB - Pedrosa, Elaine Cristina Teixeira (2008)
This work aims to identify the environmental vulnerability of the Gramame river basins in the upstream of the Gramame-Mubamba reservoir seeking guide for a better planning of land use. This reservoir provides water supplies for the cities os Pedras-de-Fogo, Conde and so-called Great João Pessoa, witch comprises the municipalities of João Pessoa, Cabedelo, Bayeux, and part of Santa Rita. The study area is located in the southern portion of Zona da Mata of Paraiba, brazillian northeast, has an area of 254, 4 km2, inserting itself partially in the municipalities of Pedras de Fogo, Santa Rita and Alhandra. It was applied in this study the same methodology used in the Ecological-Economic Zoning EEZ, according to the theory of ecodynamics, to generate the environmental vulnerability map. This methodology uses information from the physical environment related to the following themes: geology, geomorphology, pedology, vegetation and land use and climate, where for each theme are defined intervals of vulnerability. Posteriorly thematic maps are converted in numerical grids, witch are integrated in environments of Geographical Information System GIS, using a technique of geographical analysis called of algebra of maps. Based on this map it was possible to identify the most vulnerable areas of the watersheds, these areas located in the bottom of the valleys and in the most pronounced slopes located near the headwaters of Gramame and Mubamba rivers.